(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article questions the academic-artistic research practice of performing arts about mimes and masks in relation to afro-Brazilian cultural practices from decolonial discussions about racial democracy and cultural appropriation. The intention is to question if the apprehension of a south-American decolonial thought developed in the continent’s Hispanic zone is effective without taking into account the specificities of Brazilian racism in the society as a whole.